Impacto da asma na qualidade de vida de escolares do município de Ijuí/RS - Strassburger, Simone Zeni (2014)
Objective : Evaluate the impact of asthma on the quality of life in a population of school children in the city of Ijuí, which is located in an essentially agricultural region of the state of Rio Grande do Sul, Brazil. As well as the relationships between the comorbidities of atopy and rhinoconjunctivitis. Methods : Transversal study of children in elementary school from third through eighth grades in the municipality of Ijuí, Rio Grande do Sul, Brazil. In November 2012 (phase I), parents or guardians of the school children population answered an initial screening questionnaire. Based on it, asthmatic children were classified and paired with non-asthmatics considering parameters, such as age, gender and school. From May to June 2013 (Phase II), at their residency, parents or guardians and school children were interviewed and answered questions related to asthma, rhinitis and rhinoconjunctivitis of the International Study of Asthma and Allergies in Childhood questionnaire. An additional set of questions related to quality of life and asthma control were included on the questionnaire. A group of children, asthmatic and non- asthmatic (control), were subjected to blood tests to evaluate atopy through IgE levels. Results: In the first phase of the study, 2,000 initial screening questionnaires were distributed, out of which 1,691 (84.5%) were completed; school children aged on average 11.5 years and 780 (46%) were males. According to the criteria utilized on this study, 324 (19%) of the school children were classified as having active asthma. Questions about asthma, respiratory symptons and questionnaire about quality of life were answered by 480 school children. Out of which, 246 (51,2%) presented rhinoconjunctivitis in the past year. 189 school children were classified as asthmatic and 291 as healthy controls. 185 school children consented to be subjected to blood tests, out of which 127 (68,6%) were considered allergic to at least one of the tested allergens. Assessing the domains of quality of life, the asthmatic group presented the worst scores on the physical domain (p ˂0,001) and on the total quality of life (p=0,025) when compared to the control group. The average scores of quality of life for the group of school children with asthma and rhinoconjunctivitis was significantlly lower on the same domains: physical (p˂0,001) and total quality of life (p= 0,018), when compared to its controls presenting the same symptoms. Considering the group of asthmatic school children with or without rhinoconjunctivitis, the average scores were lower in the physical (p=0,039) and emotional (p=0,025) domains for the group with asthma and rhinoconjunctivitis. Multivariate analysis of health-related quality of life, revelead a significant association between asthma diagnosis and total score (β=-2,59 CI95% -4,82 a -0,37 p=0,022). The asthma control test revealed that 62(50,4%) were not controlling the disease. Evaluating the correlation between the asthma control test and the domains of quality of life, weak statistically significant positive correlations between the physical domain score (r= 0,38; p˂0,001) and total scores(r=0,24; p=0,008) were found. Conclusion : The health-related quality of life in children with asthma was lower when compared to the control group. The rhinoconjunctivitis as an asthma comorbidity seems to affect health-related quality of life, especially in physical domain, but asthma is the major contribuitor to a decreased quality of life.